Akkermansia muciniphila strain ATCC BAA-835 does not promote short-term intestinal inflammation in gnotobiotic interleukin-10-deficient mice. (4th March 2019) - Ring, Christiane; Klopfleisch, Robert; Dahlke, Katja; Basic, Marijana; Bleich, André; Blaut, Michael
ABSTRACT: Akkermansia muciniphila is a common member of the intestinal microbiota of healthy human individuals. Its abundance is negatively associated with inflammatory bowel disease and metabolic disorders and the oral administration of A. muciniphila improves the symptoms of metabolic disease in mice. Therefore, A. muciniphila is a promising candidate for the treatment of type-2 diabetes and obesity. However, some studies using animal models of intestinal inflammation reported that A. muciniphila may exacerbate gut inflammation. Because of these contradictory reports the present study aimed to clarify the role of A. muciniphila in the development of intestinal inflammation and the conditions promoting it. For this purpose, the short-term colitogenic potential of A. muciniphila strain ATCC BAA-835 was investigated in colitis-prone, gnotobiotic IL-10-deficient ( Il10 -/- ) mice. Il10 -/- mice mono-associated with A. muciniphila showed no signs of intestinal inflammation based on body-weight change, histopathological scoring and inflammatory markers. Additional association of the mice with the colitogenic Escherichia coli strain NC101 led to cecal but not colonic inflammation. However, the severity of the inflammation did not exceed that observed in mice mono-associated with E. coli NC101. Il10 -/- mice colonized with a simplified human intestinal microbiota showed increased histopathology, but no increase in inflammatory markers. Furthermore, co-colonization with A. muciniphila did not modify histopathology. The turnover of intestinal mucus was similar in all groups despite the mucus-degrading property of A. muciniphila . Overall, the data do not support a short-term pro-inflammatory effect of A. muciniphila strain ATCC BAA-835 in the Il10 -/- mouse model for inflammatory bowel disease.